Corporate social responsibility in business practices of multinational companies: study of differences between Czech and Slovak - Renata Skýpalová; Jana Kozáková; Mária Urbánová; Vito de Sabato (Business, Management and Economics Engineering, 2023)
Purpose – find differences in the core principles of implementation of CSR (Corporate Social Responsibility) practices in subsidiaries of foreign multinationals in Slovak and Czech Republic, two similar yet different countries.